Multi-Scale Control: Improved Technique to Overcome Time-Delay Limitation - Nandong, Jobrun; Zang, Zhuquan (IEEE Xplore, 2013)
This paper presents a general multi-scale control scheme which can be used to control processes with significant time-delays. The salient feature of the multi-scale control scheme is to decompose a given plant into a sum of basic factors or modes. An individual sub-controller is specifically designed to control each of the plant modes and subsequently, an overall multi-scale controller is synthesized via combining all of the sub-controllers in a manner to enhance cooperation among these different plant modes. Numerical examples show that the multi-scale control scheme can provide improved performance and robustness over the conventional single-loop PID and Smith predictor schemes.